THE CHARACHTERISTIC OF STRESS-FACTORS THAT CAUSE THE EMERGING OF THE POST TRAUMATIC STRESS DISORDERS IN SERVICEMEN THE COMBATANTS - Bryndikov, Yuriy (Social work and education, 2017)
It is analyzed in the article the general approaches to the problem of post-traumatic stress disorders in servicemen the combatants. There are stress and post-traumatic stress disorders among the destructive psychological states of servicemen who have been in the ATO zone. While researching it is analyzed the scientists’ approaches to the essence of the concept of “stress” that is a general protective reaction of the organism to the negative environmental influences.It is characterized the post-traumatic stress disorder as anxiety disorder that occurs after psychological stress, various traumatic events. It is established that post-traumatic stress disorder can be manifested in different ways. Here are presented the forms of post-traumatic stress disorder’s manifestation. The main weakness is memory, increased alertness, thoughts of suicide, feeling of constant tiredness. The attention is focused on the combat stress – a combination of emotions due to prolonged life threatening in a combat environment. There are described the stress-factors of combat stress such as predisposition to influences that threaten life; Predisposition to violence; Participation in the processes accompanied by brutal violence. Different approaches are presented for the identification of stress factors that cause military psychological trauma.